PENGARUH PERTUMBUHAN PENDUDUK TERHADAP PERSENTASE KEMISKINAN MELALUI PENDAPATAN PER KAPITA DI INDONESIA PERIODE 2011-2018 (Pendekatan Nilai Ilmu Positif Dan Nilai Islami) - Rifa'i, M Anwar; Yuliana`, Indah; Khasanah3, Umrotul; As’ari, Erham (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2021)
This research had the main aims, which is to analyze the indirect effect of population growth toward the percentage of poverty through income per capita. From these main aims, this research expanded so that it raised three basic formulas as a premise namely the direct effect of population growth toward the percentage of poverty, population growth toward income per capita, income per capita toward the percentage of poverty. The population in this study was the country of Indonesia with 34 provinces as a sample, in the 2011-2018 period. The secondary data compiled from the Badan Pusat Statistik (BPS) Indonesia that contains two dimensions of the unit and time. The analysis method used was path analysis withs Stata Software. This study showed four results of the analysis, namely: population growth does not significantly influence the percentage of poverty, population growth has a significant positive effect on per capita income, income per capita has a significant negative effect on the percentage of poverty, and population growth has a negative and significant indirect effect on the percentage of poverty through income per capita.